2019
DOI: 10.1021/acsenergylett.9b02361
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State Infrared Upconversion in Perylene Diimides Followed by Direct Electron Injection

Abstract: In this contribution we demonstrate a solid-state approach to triplet−triplet annihilation upconversion for application in a solar cell device in which absorption of near-infrared light is followed by direct electron injection into an inorganic substrate. We use time-resolved microwave photoconductivity experiments to study the injection of electrons into the electron-accepting substrate (TiO 2 ) in a trilayer device consisting of a triplet sensitizer (fluorinated zinc phthalocyanine), triplet acceptor (methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…31). 45 Although, the absorbed photon to injected electron efficiency for this system was low (1.8%), it provided a new route for practical fabrication of solid state TTA-UC to solar cells beyond deoxygenated organic solvents. 1,2 The low UC quantum yield obtained with NIR to Vis solid state TTA-UC systems is one of the key issues impeding their integration to the photovoltaic devices.…”
Section: Solid State Nir To Vis Molecular Tta-ucmentioning
confidence: 99%
See 1 more Smart Citation
“…31). 45 Although, the absorbed photon to injected electron efficiency for this system was low (1.8%), it provided a new route for practical fabrication of solid state TTA-UC to solar cells beyond deoxygenated organic solvents. 1,2 The low UC quantum yield obtained with NIR to Vis solid state TTA-UC systems is one of the key issues impeding their integration to the photovoltaic devices.…”
Section: Solid State Nir To Vis Molecular Tta-ucmentioning
confidence: 99%
“…Grozema's research group has demonstrated the application of solid state NIR to Vis TTA-UC to dye sensitized solar cell. 45 The TTA-UC fabricated solar cell was comprised of a trilayer structure (sensitizer-annihilator-electron acceptor) wherein, crystalline layers of TTA-UC couple (fluorinated zinc phthalocyanine) (F 16 ZnPc)/methyl substituted perylenediimide (PDI-CH 3 ) were deposited on a polycrystalline layer of TiO 2 (electron acceptor). The excitation of sensitizer layer with NIR light (700 nm), resulted in an injection of electron from upconverted singlet excited state of annihilator into the conduction band of TiO 2 , measured by photoconductance signals (Fig.…”
Section: Solid State Nir To Vis Molecular Tta-ucmentioning
confidence: 99%
“…Recently, NIR-to-visible upconversion system containing fluorinated zinc phthalocyanine (F16ZnPc, Figure 5b) as the sensitizer and perylenetetracarboxylic acid diimide (PDI-CH 3 , Figure 5a) as the annihilator was deposited on the top of TiO 2 layer. [205] Under the NIR light (709 nm) excitation, triplets generated in F16ZnPc was efficiently transferred to PDI-CH 3 . Consequently, electrons formed from the upconverted singlet excited-states of PDI-CH 3 are directly injected into TiO 2 .…”
Section: Solid-state Tta Upconversion Integrated Photovoltaicsmentioning
confidence: 99%
“…Moreover, intersystem crossing leading to population of the photosensitizer’s lowest-lying triplet excited state must be rapid, and one usually faces the challenge that undesired nonradiative relaxation processes become increasingly important the lower the triplet energy gets . So far, mostly certain carefully designed osmium, palladium, , and platinum complexes fulfill the necessary requirements for red-light absorbing triplet sensitizers, whereas base metal complexeswith the exception of some Cu­(I) and Zn­(II) compounds have remained underexplored in this context …”
Section: Introductionmentioning
confidence: 99%